Left ventricular remodelling in bicuspid aortic valve disease. (30th December 2021) - Butcher, Steele C; Pio, Stephan M; Kong, William K F; Singh, Gurpreet K; Ng, Arnold C T; Perry, Rebecca; Sia, Ching-Hui; Poh, Kian Keong; Almeida, Ana G; González, Ariana; Shen, Mylène; Yeo, Tiong Cheng; et al.
Abstract: Aims: Characterization of left ventricular (LV) geometric pattern and LV mass could provide an important insight into the pathophysiological adaptations of the LV to pressure and/or volume overload in patients with bicuspid aortic valve (BAV) and significant (≥moderate) aortic valve (AV) disease. This study aimed to characterize LV remodelling and its prognostic impact in patients with BAV according to the predominant type of valvular dysfunction. Methods and results: In this international, multicentre BAV registry, 1345 patients [51.0 (37.0–63.0) years, 71% male] with significant AV disease were identified. Patients were classified as having isolated aortic stenosis (AS) ( n = 669), isolated aortic regurgitation (AR) ( n = 499) or mixed aortic valve disease (MAVD) ( n = 177). LV hypertrophy was defined as a LV mass index >115 g/m 2 in males and >95 g/m 2 in females. LV geometric pattern was classified as (i) normal geometry: no LV hypertrophy, relative wall thickness (RWT) ≤0.42, (ii) concentric remodelling: no LV hypertrophy, RWT >0.42, (iii) concentric hypertrophy: LV hypertrophy, RWT >0.42, and (iv) eccentric hypertrophy: LV hypertrophy, RWT ≤0.42. Patients were followed-up for the endpoints of event-free survival (defined as a composite of AV repair/replacement and all-cause mortality) and all-cause mortality. Type of AV dysfunction was related to significant variations in LV remodelling. Higher LV mass index, i.e. LV hypertrophy, was independently associated with the composite endpoint for patients with isolated AS [hazard ratio (HR) 1.08 per 25 g/m 2, 95% confidence interval (CI) 1.00–1.17, P = 0.046] and AR (HR 1.19 per 25 g/m 2, 95% CI 1.11–1.29, P < 0.001), but not for those with MAVD. The presence of concentric remodelling, concentric hypertrophy and eccentric hypertrophy were independently related to the composite endpoint in patients with isolated AS (HR 1.54, 95% CI 1.06–2.23, P = 0.024; HR 1.68, 95% CI 1.17–2.42, P = 0.005; HR 1.59, 95% CI 1.03–2.45, P = 0.038, respectively), while concentric hypertrophy and eccentric hypertrophy were independently associated with the combined endpoint for those with isolated AR (HR 2.49, 95% CI 1.35–4.60, P = 0.004 and HR 3.05, 95% CI 1.71–5.45, P < 0.001, respectively). There was no independent association observed between LV remodelling and the combined endpoint for patients with MAVD. Conclusions: LV hypertrophy or remodelling were independently associated with the composite endpoint of AV repair/replacement and all-cause mortality for patients with isolated AS and isolated AR, although not for patients with MAVD. Graphical Abstract: